Peri-operative management of neuromuscular blockade: A guideline from the European Society of Anaesthesiology and Intensive Care. Issue 2 (15th February 2023) - Fuchs-Buder, Thomas; Romero, Carolina S.; Lewald, Heidrun; Lamperti, Massimo; Afshari, Arash; Hristovska, Ana-Marjia; Schmartz, Denis; Hinkelbein, Jochen; Longrois, Dan; Popp, Maria; de Boer, Hans D.; Sorbello, Massimiliano; et al.
Abstract : Recent data indicated a high incidence of inappropriate management of neuromuscular block, with a high rate of residual paralysis and relaxant-associated postoperative complications. These data are alarming in that the available neuromuscular monitoring, as well as myorelaxants and their antagonists basically allow well tolerated management of neuromuscular blockade. In this first European Society of Anaesthesiology and Intensive Care (ESAIC) guideline on peri-operative management of neuromuscular block, we aim to present aggregated and evidence-based recommendations to assist clinicians provide best medical care and ensure patient safety. We identified three main clinical questions: Are myorelaxants necessary to facilitate tracheal intubation in adults? Does the intensity of neuromuscular blockade influence a patient's outcome in abdominal surgery? What are the strategies for the diagnosis and treatment of residual paralysis? On the basis of this, PICO (patient, intervention, comparator, outcome) questions were derived that guided a structured literature search. A stepwise approach was used to reduce the number of trials of the initial research ( n = 24 000) to the finally relevant clinical studies ( n = 88). GRADE methodology (Grading of Recommendations, Assessment, Development and Evaluation) was used for formulating the recommendations based on the findings of the included studies in conjunction with their methodological quality. A two-step Delphi process was used to determine the agreement of the panel members with the recommendations: R1 We recommend using a muscle relaxant to facilitate tracheal intubation (1A). R2 We recommend the use of muscle relaxants to reduce pharyngeal and/or laryngeal injury following endotracheal intubation (1C). R3 We recommend the use of a fast-acting muscle relaxant for rapid sequence induction intubation (RSII) such as succinylcholine 1 mg kg −1 or rocuronium 0.9 to 1.2 mg kg −1 (1B). R4 We recommend deepening neuromuscular blockade if surgical conditions need to be improved (1B). R5 There is insufficient evidence to recommend deep neuromuscular blockade in general to reduce postoperative pain or decrease the incidence of peri-operative complications. (2C). R6 We recommend the use of ulnar nerve stimulation and quantitative neuromuscular monitoring at the adductor pollicis muscle to exclude residual paralysis (1B). R7 We recommend using sugammadex to antagonise deep, moderate and shallow neuromuscular blockade induced by aminosteroidal agents (rocuronium, vecuronium) (1A). R8 We recommend advanced spontaneous recovery (i.e. TOF ratio >0.2) before starting neostigmine-based reversal and to continue quantitative monitoring of neuromuscular blockade until a TOF ratio of more than 0.9 has been attained. (1C)